2012
DOI: 10.1162/pres_a_00111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stereoscopic Viewing on Presence, Anxiety, and Cybersickness in a Virtual Reality Environment for Public Speaking

Abstract: In this study, we addressed the effect of stereoscopy on presence, anxiety, and cybersickness in a virtual public speaking world, and investigated the relationships between these three variables. Our results question the practical relevance of applying stereoscopy in head-mounted displays (HMDs) for virtual reality exposure therapy (VRET) in a virtual public speaking world. In VRET, feelings of presence improve the efficacy (B. K. Wiederhold & M. D. Wiederhold, 2005). There are reports of a relatively larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 43 publications
0
34
2
7
Order By: Relevance
“…Two more studies investigated social stress. Ling et al (2012) tested the effect of stereoscopic vs. non-stereoscopic presentation of a VR public speaking environment in a crossover design. HR increased signifi cantly during the speaking task in both conditions, which did not differ.…”
Section: Habituation Effectsmentioning
confidence: 99%
“…Two more studies investigated social stress. Ling et al (2012) tested the effect of stereoscopic vs. non-stereoscopic presentation of a VR public speaking environment in a crossover design. HR increased signifi cantly during the speaking task in both conditions, which did not differ.…”
Section: Habituation Effectsmentioning
confidence: 99%
“…co-presence) have been found for similar applications involving interaction with virtual characters, e.g. for public speaking therapy [20]. Furthermore, requiring users to wear 3D glasses presented a logistical challenge to ensure that glasses were always available.…”
Section: Kioskmentioning
confidence: 99%
“…PSA, a subtype of social phobia, which can be a destructive disorder among novice software engineers. Such individuals might have excessive concerns about being embarrassed and judged by other people [44]. Some research indicated that subjects exposed to the feared social situations and learnt to modify their thoughts and behaviors show decreased anxious symptoms [45].…”
Section: Discussionmentioning
confidence: 99%